New perspectives : portfolio projects for business communication - Cram, Carol M. (Cengage Learning, 2010)
Helps students learn how to create a wide range of business documents and oral presentations, use technology to communicate effectively, address the needs of diverse audiences, and consider the ethical implications of their communication practices